Riding the Waves of Change: Developing Managerial Competencies for a Turbulent WorldRiding the Waves of Change: Developing Managerial Competencies for a Turbulent World, by MorganGareth. San Francisco: Jossey-Bass, 1988, 213 pp., cloth. - Siehl, Caren (Academy of Management Review, 1989)
The article reviews the book “Riding the Waves of Change: Developing Managerial Competencies for a Turbulent World,” by Gareth Morgan.